2013
DOI: 10.1080/14697688.2011.647054
|View full text |Cite
|
Sign up to set email alerts
|

Modelling microstructure noise with mutually exciting point processes

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
318
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(326 citation statements)
references
References 48 publications
6
318
0
2
Order By: Relevance
“…The debate about the endogenous and exogenous component of price dynamics has recently received a new impulse thanks to the application of Hawkes processes to the modeling of financial data [8][9][10][11][12][13][14][15]. Hawkes processes [16], originally introduced in seismology, describe a point (counting) process where the intensity is not constant but depends on the past history of the counting process, weighted by a suitably chosen kernel.…”
Section: Introductionmentioning
confidence: 99%
“…The debate about the endogenous and exogenous component of price dynamics has recently received a new impulse thanks to the application of Hawkes processes to the modeling of financial data [8][9][10][11][12][13][14][15]. Hawkes processes [16], originally introduced in seismology, describe a point (counting) process where the intensity is not constant but depends on the past history of the counting process, weighted by a suitably chosen kernel.…”
Section: Introductionmentioning
confidence: 99%
“…Ogata, 1981;Moller and Rasmussen, 2005, and Appendix A), allowing further developments for the use of the estimated models. These practical properties make Hawkes processes good candidates for the study of the clustering of events empirically observed in order book models (Hautsch, 2004;Bowsher, 2007;Large, 2007;Bacry et al, 2012).…”
Section: Testing the Calibrationmentioning
confidence: 99%
“…For example, these self-and mutually exciting point processes can model arrival times of orders in an order book model (Large, 2007;Muni Toke, 2011), or explain the Epps effect in a microstructure toy model (Bacry et al, 2012). An econometric framework has been derived by Bowsher (2007).…”
Section: Introductionmentioning
confidence: 99%
“…This class of point processes has wide applications in many different fields, primarily in seismology (Hawkes & Oakes 1974, Ogata 1988, and more recently in finance (Bowsher 2007, Dassios et al 2011, Embrechts et al 2011, Bacry et al 2012, Bacry et al 2013). In the context of EVT, a univariate Hawkes-POT process was introduced by Chavez-Demoulin et al (2005), and more recently reviewed in Chavez-Demoulin & McGill (2012).…”
Section: The Multivariate Hawkes-pot Modelmentioning
confidence: 99%
“…erates a flexible and computationally tractable multivariate dependence structure, properties that are empirically well-documented (Bowsher 2007, Hall & Hautsch 2007, Hautsch 2011, Bacry et al 2012, Bacry et al 2013.…”
Section: Introductionmentioning
confidence: 99%